A Neophyte's Journey through Qualitative Analysis Using Morse's Cognitive Processes of Analysis - Rachel Walker RN, BA, BN, MN; Marie Cooke RN, DAppSc, BAppSc, MSPD, PhD; Margaret McAllister RN, RPN, DipAppSci-Nurs, BA, MEd, EdD (International Journal of Qualitative Methods, 2008)
Abstract: In the early stages of her master's thesis the author became increasingly concerned about how she would analyze the data for her planned critical interpretive study. She felt that she needed clear direction about the process of qualitative analysis but found the “how to” of theory development within qualitative data analysis poorly described and vague. A book chapter by qualitative researcher Janice Morse (1994) provided guidance. In it Morse outlined four cognitive and essentially sequential processes, which the author adapted to guide the analysis of data for her study.